A Review of Air Quality and Concentrations of Air Pollutants in Nigeria - I.B. Abaje; Y. Bello; S.A. Ahmad (Journal of Applied Sciences and Environmental Management, 2020)
This study generally classifies air pollutants on the basis of: primary or secondary, natural or anthropogenic, chemical composition, physical state, and the space scales of their effects. Air pollutants that affect air quality in Nigeria were discussed based on natural and anthropogenic sources. The natural sources include: sand dust, sea spray, volcanic activities, smoke and carbon monoxide from wildfires among others, while the anthropogenic sources include: vehicular emissions, mining activities, industries such as cement companies and quarry factories, agricultural practices and solid waste dumps among others. Some of the atmospheric pollutants that posed greatest threat to human health were equally examined. They include: Sulphur dioxide (SO2) which can react with water vapor (H2O) in the atmosphere to form sulphuric acid (H2SO4) and thus acid rain; particulate matter (PM) with less than 10 μm, particularly fine particles (PM2.5 ) and particles in the fine fraction that are smaller than 0.1 μm (ultrafine particles), can carry toxic chemicals which are linked to cancer; carbon monoxide (CO), even in very small concentrations, can prevent oxygen from being delivered through the body major organs; ozone which is a highly reactive gas causes oxidation of a number of macromolecules within a biological system and produces free radicals that can damage DNA molecules and cause carcinogenesis. Based on the aforementioned, this study recommends that priority should be given to the establishment of air monitoring stations in all urban centers of the country in order to provide accurate and continuous information on air quality.